2019
DOI: 10.1590/1983-21252019v32n115rc
|View full text |Cite
|
Sign up to set email alerts
|

Germination and Vigour in Seeds of the Cowpea in Response to Salt and Heat Stress

Abstract: Salinity is prejudicial to plant development, causing different types of damage to species, or even between genotypes of the same species, with the effects being aggravated when combined with other types of stress, such as heat stress. The aim of this study was to evaluate the tolerance of cowpea genotypes (Vigna unguiculata L. Walp.) to salt stress at different temperatures. Seeds of the Pujante, Epace 10 and Marataoã genotypes were placed on paper rolls (Germitest®) moistened with different salt concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…The initial seedling length not differ between cultivars (SL), obtaining an average value of 17.73 cm. Similar results were found in a study by Nunes et al (2019) when evaluating the effect of temperature on cowpea genotypes, which found that there was no significant difference in the initial seedling length of the evaluated genotypes, regardless the temperature regime. The initial dry weight of the seedling was higher for cv.…”
Section: Resultssupporting
confidence: 88%
“…The initial seedling length not differ between cultivars (SL), obtaining an average value of 17.73 cm. Similar results were found in a study by Nunes et al (2019) when evaluating the effect of temperature on cowpea genotypes, which found that there was no significant difference in the initial seedling length of the evaluated genotypes, regardless the temperature regime. The initial dry weight of the seedling was higher for cv.…”
Section: Resultssupporting
confidence: 88%
“…Maia et al (2012) found that root length was reduced between 25 and 56%, depending on the cultivar, when comparing 100 mM NaCl concentration to the control treatment. Nunes et al (2019) observed that the cultivar BRS Marataoã showed a reduction in root length at the stress level corresponding to 10 mM NaCl, showing high sensitivity to salt stress. For the concentration of 200 mM of NaCl, Deuner et al (2011) observed that there was only the beginning of primary root protrusion, not being possible to measure this character.…”
Section: Resultsmentioning
confidence: 93%
“…Therefore, applying heat stress throughout the crop's development cycle may be advisable to better understand the physiological and genetic basis of cowpea's response to heat stress. High temperatures could impact seed germination and seedling survival for cowpea, especially when seeds are sown deep into the soil [39] and in soils with high salinity [17]. Even when cowpea seeds can survive up to 50 • C day temperatures with an adequate water supply and still produce substantial vegetative biomass [6], their vegetative growth can be impacted negatively by heat stress [9,15,21].…”
Section: Impacts Of Heat Stresses and Tolerance Mechanisms In Cowpeamentioning
confidence: 99%
“…The crop thrives in relatively high-temperature environments [6, 12,13] compared with other legumes. However, during its reproductive phase, cowpea is especially vulnerable to heat stress, resulting in significant yield losses [6,14,15], even though most genotypes have substantially elevated temperature tolerance during the germination and vegetative phases [15][16][17]. A 1 • C increase in night temperature above 16.5 • C between seedling emergence and first flowering has been observed to cause up to a 13.6% decrease in cowpea grain yield [18,19].…”
Section: Introductionmentioning
confidence: 99%